2021
DOI: 10.1109/access.2021.3053144
|View full text |Cite
|
Sign up to set email alerts
|

Room-Level Localization System Based on LoRa Backscatters

Abstract: The aim of this paper is to propose a novel room-level localization approach to locate LoRa backscatter devices, which can be easily embedded into wearable devices or smartphones. The advantages of this system lie in its series of low-cost, low-power, low-complexity and long-range features. LoRa backscattering operates by alternatively connecting an antenna, through a switch, to two loads with high reflection coefficients and opposite phase. The result is a frequency shift of the LoRa incident signal equal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…The weak signal received by the gateway leads to location estimation error. Many different studies try to improve the location estimation by selecting the GWs that are not affected by non-Gaussian noise [59][60][61][62]. The authors in [59] For location estimation using RSSI, different ML methods are proposed.…”
Section: Localization Accuracy Improvement Methodsmentioning
confidence: 99%
“…The weak signal received by the gateway leads to location estimation error. Many different studies try to improve the location estimation by selecting the GWs that are not affected by non-Gaussian noise [59][60][61][62]. The authors in [59] For location estimation using RSSI, different ML methods are proposed.…”
Section: Localization Accuracy Improvement Methodsmentioning
confidence: 99%
“…In [20], a wide-range localization method using LoRa backscatters based on a fingerprint method and machine learning classifiers is proposed. The first requirement of the system is the installation of LoRa receivers distributed in each room.…”
Section: Wireless Measurement and Positioningmentioning
confidence: 99%
“…Traditional RF transmitters have a power consumption several orders of magnitude higher than that consumed by backscatter transmitters and, on the contrary, the communication becomes unidirectional. Examples of applications of backscatter communications have been proposed in the literature [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the high sensitivity of LoRa receivers, which use chirp spread spectrum techniques, allows a communication range of several kilometers in line-of-sight (LoS) environments [ 23 ] and works correctly in high path loss environments. The authors have already demonstrated the feasibility of indoor communications using LoRa backscatters for location applications [ 24 , 25 ] and the feasibility to read data from deep implanted devices [ 26 ].…”
Section: Introductionmentioning
confidence: 99%